Registro da prática do cuidado farmacêutico em hospitais brasileiros antes e durante a pandemia de Covid-19 - Mascarenhas, Mylenne Borges Jácome (2024)
The documentation and registration process is fundamental to the development of clinical services provided by pharmacists. The practice of pharmaceutical care needs to be consolidated with registration in the patient's medical record. The study aimed to evaluate the practice of recording pharmaceutical care in Brazilian hospitals before and during the Covid-19 pandemic. This is an exploratory, survey-type study with a quantitative approach (absolute and relative frequency, Friedman's ANOVA and Fisher's exact test) and qualitative approach (Word Cloud (WC) and Descending Hierarchical Classification (DHC) using the “Iramuteq” software). The research was carried out electronically, from May to October 2022, with a questionnaire validated by experts. The sample was composed of clinical pharmacists who provided pharmaceutical care to patients in Brazilian hospitals, before and during the Covid-19 pandemic. 314 responses were obtained. The majority of respondents were female, 70% (n=220), and specialized in clinical pharmacy, totalizing 50.3% (n=158). A percentage of 49% (n=154) allocated more than 50% of their working hours to the practice of pharmaceutical care. Analyzing the nature of the work institution, a predominance of public institutions was found, 58.3% (n=183). During the pandemic period, the proportion of registrations in different modalities increased (p-value = 0.019). There was an increase in registration in the electronic medical record during the pandemic period (p<0.001), going from 66.9% (n=210) to 78.7% (n=247). These results were significant in the Clinical and Pediatric ICU, and in Transplant Nursery. The majority of pharmacists, 58% (n=187), demonstrated that they had some type of fear to register in the medical record, mainly those related to conflicts with other health professionals. Regarding actions that favor this registration, 64.6% (n=203) indicated training for pharmacists. In the “Word Cloud” the words presented the highest relative frequency: patient (n=30), electronic (n=30) and record (n=29). The DHC analysis generated four classes that were named: Pharmaceutical Registration; Coping with Covid-19; Pharmaceutical Services and Evidence-Based Information. There was an increase in electronic recording in the patient's medical record during the Covid-19 pandemic, and the implementation of pharmaceutical services, however, there are still challenges to be overcome. It is understood that the pharmacist is qualified to register the practice of pharmaceutical care in the patient's medical record, requiring training that seeks to restore safety, autonomy and professional development, combined with the harmonization of conduct.